A comparison of two methods for moving through a virtual environment: walking in place and interactive redirected walking - Banakou, Domna; Slater, Mel (Frontiers in Virtual Reality, 2023)
Moving through a virtual environment that is larger than the physical space in which the participant operates has been a challenge since the early days of virtual reality. Many different methods have been proposed, such as joystick-based navigation, walking in place where the participant makes walking movements but is stationary in the physical space, and redirected walking where the environment is surreptitiously changed giving the illusion of walking in a long straight line in the virtual space but maybe a circle in the physical space. Each type of method has its limitations, ranging from simulator sickness to still requiring more physical space than is available. Stimulated by the COVID-19 lockdown, we developed a new method of locomotion which we refer to as interactive redirected walking. Here, the participant really walks but, when reaching a boundary, rotates the virtual world so that continuation of walking is always within the physical boundary. We carried out an exploratory study to compare this method with walking in place with respect to presence using questionnaires as well as qualitative responses based on comments written by the participants that were subjected to sentiment analysis. Surprisingly, we found that smaller physical boundaries favor interactive redirected walking, but for boundary lengths more than approximately 7 adult paces, the walking-in-place method is preferable.